2021
DOI: 10.21203/rs.3.rs-407435/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Commemorating One-Year of the COVID-19 Pandemic: Indonesian and International Issues of Secondary and Tertiary Mathematics Learning

Abstract: A year into the COVID-19 crisis has revealed massive and substantial changes in the world of education. Educators have had to quickly develop effective online learning environments for their students. This study focuses specifically on mathematics learning issues during this first pandemic year. A systematic literature study using a scope review approach was conducted to capture issues on a national and international scale in the context of secondary and tertiary education. Through the identification of nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
(71 reference statements)
2
3
0
Order By: Relevance
“…However, they eventually perceived the transition positively as Salsa explained that her online learning habit was very bad and that she hoped to improve it through offline learning so that she began to see the transition positively, which she was not accustomed to it at first because some things she had previously been comfortable with were changed. This finding was related to previous study who found that in their study, there were groups in which students had previously been in their comfort zone and accustomed to the life habits in terms of preparation before class including sleep routine which has an effect on learning motivation (Soesanto & Dirgantoro, 2021). The drawbacks of online learning which influenced the perception of the participants in this study were the same as in the study that found that the students might enjoy the flexibility and independence of online learning as a result of the possibilities dishonesty in finishing the assignment which was very dangerous as it would lead to the laziness (Sadikin & Hamidah, 2020).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, they eventually perceived the transition positively as Salsa explained that her online learning habit was very bad and that she hoped to improve it through offline learning so that she began to see the transition positively, which she was not accustomed to it at first because some things she had previously been comfortable with were changed. This finding was related to previous study who found that in their study, there were groups in which students had previously been in their comfort zone and accustomed to the life habits in terms of preparation before class including sleep routine which has an effect on learning motivation (Soesanto & Dirgantoro, 2021). The drawbacks of online learning which influenced the perception of the participants in this study were the same as in the study that found that the students might enjoy the flexibility and independence of online learning as a result of the possibilities dishonesty in finishing the assignment which was very dangerous as it would lead to the laziness (Sadikin & Hamidah, 2020).…”
Section: Discussionsupporting
confidence: 81%
“…The research discovered that for a specific topic, arithmetic, face-to-face is more convenient since it is also highly important for human contact, yet online learning provides a viable instructional alternative. Previous study stressed the theme of students' impressions of earlier emergency learning, restricted face-to-face transfer, and instructor expectations of the transition (Soesanto & Dirgantoro, 2021). Conducting a cross-sectional survey to obtain all of the necessary information found that participants welcomed the learning shift, which was accompanied by the hope that teachers would correctly design teaching techniques.…”
Section: Introductionmentioning
confidence: 99%
“…After reviewing the available literature, we found a poorer representation of publications at the tertiary level than the primary and secondary levels. This agrees with the findings of Soesanto et al [9]. In our opinion, there are several reasons for this.…”
Section: Introductionsupporting
confidence: 94%
“…Several studies tried to explain the impact of the rapid transition to online mathematics teaching during the pandemic on students' academic development [12][13][14][15][16][17]24,26,28]. In April 2021, Soesanto et al [9] encouraged researchers to bridge the still large research gap regarding the causality of implementing online mathematics learning in times of crisis in order to contribute to developing pedagogical strategies to improve university students' mathematics performance and attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Like teachers, students also tried to adopt and adapt with the newly implemented 'technologically infused' learning. This emergency has led to not only the development and adaptation variety of learning strategies but also occurrence of learning difficulties that urgently need to be solved (Bakker & Wagner, 2020;Soesanto & Dirgantoro, 2021b). For example, self-access learning which is commonly developed to maximize the impact of distance learning reduces students' dependence on teachers, and thus increases collaboration between students (Al Ghazali, 2020).…”
mentioning
confidence: 99%